Childhood Posterior Reversible Encephalopathy Syndrome: Clinicoradiological Characteristics, Managements, and Outcome - Chen, Tai-Heng (Frontiers in Pediatrics, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a novel clinicoradiological syndrome characterized by convulsions, headache, altered mentality, and impaired vision, which are usually accompanied by hypertension. As its nomination, PRES is usually diagnosed according to the presence of typical neuroimage showing vasogenic edema predominately involving the posterior brain area. With the widespread utilization of magnetic resonance imaging (MRI), PRES is becoming more perceptible in different medical fields. Compared to adult cases, childhood PRES seems to have a broader clinical and neuroradiological spectrum. PRES can be associated with various underlying comorbidities, medication use, and therapeutic modalities in children with diverse neurological manifestations. Moreover, pediatric patients with PRES have a more significant propensity for atypical MRI findings beyond the typically posterior cerebral areas. The knowledge of typical and atypical presentations in children is essential to avoid misdiagnosing or missing PRES, which is a potentially treatable entity. Early supportive care is the mainstay of treatment, with particular attention to the treatment of hypertension with rigorous attention to all body systems. Prompt identification and symptom-directed management are imperative to achieve a reversible prognosis in childhood PRES. Future studies specially designed for the child population are required to determine potential outcome predictors, and further, to develop novel strategies of neuroprotection in childhood PRES.